Genetic Characterizr:~tion of three Ompok species using mitochondrial DNA sequences - Malakar, A. K.; Lakra, W. S.; Singh, M.; Goswami, M.; Mishra, R. M. (Journal of Indian Fisheries Association, 2009)
Partial sequences of cytochrome b (Cyt b) and 16S ribosomal RNA {16S rRNA} mitochondrial genes were used for species identification and estimating phylogenetic relationship among three commercially important Ompok species viz. 0. pabda/ 0. pabo & 0. bimaculatus. The sequence analysis of Cyt b {1118bp) and 16S rRNA {569 & 570bp) genes revealedthat 0. pabda1 0. pabo & 0. bimacu/atus were genetically distinct species and they exhibited identical phylogenetic relationship. The present study discussed usefulness of mtDNAgenes {Cyt b & 16S rRNA) in resolving taxonomic ambiguity and estimating phylogenetics relationship.Keywords: Ompok; mtDNA gene; Cyt b; 16S rRNA; Genetic variation.